Análisis de tres métodos de control de candidatus liberibacter solanacearum en seis ecotipos de tomate de árbol solanum betaceum en etapa de desarrollo, Cusubamba – Cotopaxi 2022. - Cofre Casillas, Luis Rolando (2023)
The present research work´s aim is to analyze the behavior of purple tip caused by (Candidatus Liberibacter solanacearum), in Carrillo neighborhood, Cusubamba parish, Salcedo Canton in Cotopaxi province with an altitude of 3,000 msnm, in the cultivation of tree tomato (Solanum betaceum). The present research work´s importance is to reduce the purple tip disease, which in the Sierra region is evidenced in 2013 symptoms of PM disease. In order to identify disease-resistant ecotypes (Candidatus Liberibacter solanacearum) that is transmitted by the psyllid vector (cockerelli bactericide). Multivariate analysis about the main components identified the ecotype of resistance and tolerance to the disease called purple tip, the results resistant ecotypes for Candidatus Liberibacter solanacearum disease in the sector that were: The descendants of Belisario Quevedo without affection, Belisario Quevedo, Supermaxi Bulk and Nabuzo, who showed the most significant averages of all ecotypes. The active ingredients in particular: (Imidacloprid), (cyromazine) (formetanate), (diflubenzuron lambdacihalothrin), managed to reduce and control the incidence of eggs, nymphs, and adults, through the weekly extended level curve that could be analyzed using Excel tables, and the constant applications of every 15 dayswith the active ingredient rotation method.